Privately contributing to public goods over time: An experimental study - Werner Güth; Maria Vittoria Levati; Andreas Stiehler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
Similar to Levati and Neugebauer (2001), a clock is used by which participants can vary their individual contributions for voluntarily providing a public good. As time goes by, participants either in(de)crease their contribution gradually or keep it constant. Groups of two poorly and two richly endowed participants encounter repeatedly the weakest link-, the usual average contribution- and the best shot-technology of public good provision in a within subject-design. Some striking findings are that the weakest link-technology fares much better than the other two technologies in terms of welfare, and that the willingness to voluntarily contribute is greatly affected by the (increasing or decreasing) clock mechanism.
urn:nbn:de:kobv:11-10048761
Keywords: C72; C92; H41; D44; 330; Public goods; Voluntary contributions; Efficient provision; Clock mechanism